2022
DOI: 10.56354/jendelainovasi.v5i1.111
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Sektor Pertanian, Industri Pengolahan, Dan Pariwisata Terhadap Kemiskinan Di Jawa Tengah Tahun 2016-2020

Abstract: As a developing country, Indonesia has not been separated from the problem of poverty. Central Java is one of the provinces in Indonesia that has a high number of poor people in Indonesia. Even poverty in Central Java is still a strategic issue that cannot be completely resolved. This study was conducted with the aim of knowing the effect of the output of the agricultural sector, manufacturing industry, and the tourism sector on the number of poor people in Central Java in 2016-2020. This study uses secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…Household income between farmers who work purely in the agricultural sector and the agritourism sector shows a significant difference (Artini et al, 2022). In addition, a study conducted in Central Java found that the agricultural sector has a negative and significant effect on poverty, while the tourism sector has a negative and insignificant effect on poverty (Rohmat & Indrawati, 2022).…”
Section: Gunungkidul Regencymentioning
confidence: 99%
“…Household income between farmers who work purely in the agricultural sector and the agritourism sector shows a significant difference (Artini et al, 2022). In addition, a study conducted in Central Java found that the agricultural sector has a negative and significant effect on poverty, while the tourism sector has a negative and insignificant effect on poverty (Rohmat & Indrawati, 2022).…”
Section: Gunungkidul Regencymentioning
confidence: 99%
“…Sementara itu, jumlah wisatawan nusantara tidak berpengaruh terhadap PDRB. Kemudian, Rohmat & Indrawati (2022) dengan model yang sama menemukan bahwa sektor pertanian, industri pengolahan, dan pariwisata berpengaruh negatif terhadap kemiskinan di Jawa Tengah tahun 2016-2020.…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini sejalan dengan temuan Rohmat & Indrawati (2022), di mana sektor pertanian, industri pengolahan, dan pariwisata berpengaruh negatif terhadap kemiskinan di Jawa Tengah. Hal tersebut terjadi karena ketiga sektor tersebut memiliki kotribusi yang cukup besar bagi perekonomian di Jawa Tengah, dan output sektor pertanian dan industri pengolahan terus meningkat pada tahun 2016-2020.…”
Section: Tabel 6 Hasil Regresi Femunclassified